2007
DOI: 10.5194/npg-14-337-2007
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic scaling of remotely sensed drainage basins: the differential anisotropy scaling technique

Abstract: Abstract.We investigate the statistical properties of dendritic drainage areas from diverse geological environments (Deception Canyon, Utah and the Loess Plateau, China) using narrow band visible ASTER satellite images. We show that from 240 m to 7680 m, the isotropic (angle integrated) energy spectra E(k) of all the fields closely follow a power law form: E(k)∝k −β where k is a wave number and β a scale invariant exponent. In spite of this good isotropic scaling, images with very similar β's and similar isotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the figure, we see that the contours are fairly roundish, indicating that, to some approximation, the second‐order statistics are isotropic. Careful scale‐by‐scale analyses of the anisotropy would be rewarding (see, e.g., Pflug et al, 1993; Lewis et al, 1999; Beaulieu et al, 2007), but is outside our present scope. Analysis of the individual radiance bands revealed a degree of isotropy similar to the indices shown in Fig.…”
Section: Spectral Analysismentioning
confidence: 94%
“…In the figure, we see that the contours are fairly roundish, indicating that, to some approximation, the second‐order statistics are isotropic. Careful scale‐by‐scale analyses of the anisotropy would be rewarding (see, e.g., Pflug et al, 1993; Lewis et al, 1999; Beaulieu et al, 2007), but is outside our present scope. Analysis of the individual radiance bands revealed a degree of isotropy similar to the indices shown in Fig.…”
Section: Spectral Analysismentioning
confidence: 94%
“…Beaulieu et al . [] on the other hand estimate the GSI parameters by visually examining scatterplots describing properties of isolines in Ptrue(bold-italicktrue), presenting a method that is easy to approach but laborious when estimating parameters of more than a few fields.…”
Section: Discussionmentioning
confidence: 99%
“…Beaulieu et al . [] reported that while SIG yielded reasonable estimates for theoretical simulations with a diversity of anisotropic and statistical characteristics, it was not able to quantify the true anisotropy of many empirical fields. Consequently, they proposed a new “Differential anisotropy scaling” technique.…”
Section: Introductionmentioning
confidence: 99%